Die fiktive Institution als ästhetische Strategie: Gérard Gasiorowskis »Académie Worosis Kiga« im zeitgenössischen Kontext - Nisters, Theresa (transcript, 2019)
The »fictitious institution« as a formerly neglected form of artistic critique around 1968 that - unlike other trends of that time - did not demonstratively turn its back on the art market.